2022
DOI: 10.3389/fmed.2022.879361
|View full text |Cite
|
Sign up to set email alerts
|

Mucoid Acinetobacter baumannii enhances anti-phagocytosis through reducing C3b deposition

Abstract: Background: Multidrug resistant (MDR) Acinetobacter baumannii causes serious infections in intensive care units and is hard to be eradicated by antibiotics. Many A. baumannii isolates are identified as the mucoid type recently, but the biological characteristics of mucoid A. baumannii and their interactions with host cells remains unclear.Methods: The mucoid phenotype, antimicrobial susceptibility, biofilmforming ability, acid resistance ability, peroxide tolerance, and in vivo toxicity of clinical ICUs derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In contrast to the capsule of many pathogens (Gong et al, 2022 ; Ni et al, 2020 ; Wen et al, 2016 ), the C. jejuni capsule only offers limited protection against phagocytosis by macrophages (Kim et al, 2018 ; Myszewski & Stern, 1991 ; Sikic Pogacar et al, 2009 ; Wassenaar et al, 1997 ), including in our study with chicken and human macrophages where we only observed a slight capsule‐mediated decrease in adherence (chicken cells only) or in uptake (chicken and human cells). Furthermore, consistent with many studies that reported killing within ~6 h of C. jejuni after uptake by macrophages (Myszewski & Stern, 1991 ; Šikić Pogačar et al, 2009 ; Wassenaar et al, 1997 ; Wong et al, 2015 ), we recovered live C. jejuni only up to 3 h after phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the capsule of many pathogens (Gong et al, 2022 ; Ni et al, 2020 ; Wen et al, 2016 ), the C. jejuni capsule only offers limited protection against phagocytosis by macrophages (Kim et al, 2018 ; Myszewski & Stern, 1991 ; Sikic Pogacar et al, 2009 ; Wassenaar et al, 1997 ), including in our study with chicken and human macrophages where we only observed a slight capsule‐mediated decrease in adherence (chicken cells only) or in uptake (chicken and human cells). Furthermore, consistent with many studies that reported killing within ~6 h of C. jejuni after uptake by macrophages (Myszewski & Stern, 1991 ; Šikić Pogačar et al, 2009 ; Wassenaar et al, 1997 ; Wong et al, 2015 ), we recovered live C. jejuni only up to 3 h after phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, mucoid P. aeruginosa, A. xylosoxidans, C. albicans and two strains of A. baumannii with different colony morphologies, one being mucoid and the other with smooth rounded margins, were recovered from patient sputum culture. Both A. baumannii isolates were then cultured overnight on blood agar plates at 37 • C, and bacterial colonies were then stretched with an inoculation loop for the string test to assess their mucoidity [6]. According to Gong and colleagues [6], the two strains were classified as hypermucoid (HM) and low mucoid (LM), with viscous strings of 150 mm and 0 mm in length, respectively (Figure 1).…”
Section: Isolates and Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…Both A. baumannii isolates were then cultured overnight on blood agar plates at 37 • C, and bacterial colonies were then stretched with an inoculation loop for the string test to assess their mucoidity [6]. According to Gong and colleagues [6], the two strains were classified as hypermucoid (HM) and low mucoid (LM), with viscous strings of 150 mm and 0 mm in length, respectively (Figure 1).…”
Section: Isolates and Antimicrobial Susceptibility Testingmentioning
confidence: 99%
See 2 more Smart Citations